Experimental plant virology - Chen, Jishuang; SpringerLink (Online service). (Hangzhou [China] Zhejiang University Press Heidelberg New York Springer, 2010)
"Experimental Plant Virology? provides the updated methodology for studying the genomic characterization and mechanisms of infection, the quantitative determination as well as the diagnosis of plant pathogenic viruses. With illustrations showing viral symptoms and ultra-structures, clear and concise descriptions, the book presents the latest developments in experimental plant virology. This book is intended for researchers, university teaching staff, graduate students and undergraduates in plant science. Dr. Jishuang Chen is a professor of plant pathology at the Institute of Bioengineering, Zhejiang Sci-Tech University, China.
Gene Cloning of Cucumber Mosaic Virus and Some Related Viral Agents -- Molecular Detection of Cucumber Mosaic Virus and Other RNA Viruses Based on New Techniques -- Infectious Clones and Chimerical Recombination of Cucumber Mosaic Virus and its Satellite RNAs -- Gene Function of Cucumber Mosaic Virus and its Satellite RNA Regarding Viral-host Interactions -- Plant MicroRNAs and Their Response to Infection of Plant Viruses -- Genomic Characterization of New Viruses with Double Stranded RNA Genomes.
Electronic reproduction.
Keywords: Plant molecular virology; Electronic books